2013
DOI: 10.2147/ijn.s40521
|View full text |Cite
|
Sign up to set email alerts
|

A framework for grouping nanoparticles based on their measurable characteristics

Abstract: Background: There is a need to take a broader look at nanotoxicological studies. Eventually, the field will demand that some generalizations be made. To begin to address this issue, we posed a question: are metal colloids on the nanometer-size scale a homogeneous group? In general, most people can agree that the physicochemical properties of nanomaterials can be linked and related to their induced toxicological responses. Methods: The focus of this study was to determine how a set of selected physicochemical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Statistical analysis and machine learning methods (e.g. principal component analysis, neural networks) have also been applied to model the properties and effects of MNs (Puzyn et al, 2009b, Puzyn et al, 2009a, Toropov et al, 2007, Toropov and Leszczynski, 2006, Sayes et al, 2013, Lynch et al, 2014. Such methods were used for example in the EU-funded MODERN project with the aim to establish in silico modelling of the effects of metal and metal oxide MNs (Liu et al, 2013b, Liu et al, 2014, Liu et al, 2013a, Gómez et al, 2013.…”
Section: Hazard Assessment Toolsmentioning
confidence: 99%
“…Statistical analysis and machine learning methods (e.g. principal component analysis, neural networks) have also been applied to model the properties and effects of MNs (Puzyn et al, 2009b, Puzyn et al, 2009a, Toropov et al, 2007, Toropov and Leszczynski, 2006, Sayes et al, 2013, Lynch et al, 2014. Such methods were used for example in the EU-funded MODERN project with the aim to establish in silico modelling of the effects of metal and metal oxide MNs (Liu et al, 2013b, Liu et al, 2014, Liu et al, 2013a, Gómez et al, 2013.…”
Section: Hazard Assessment Toolsmentioning
confidence: 99%
“…The NanoMILE approach is founded on previous work by Sayes et al (2013) demonstrating the feasibility of grouping of NMs based on combinations of related physico-chemical properties. Using principal component analysis (PCA) and linear discriminant analysis, Sayes et al assessed which properties of a set of selected physico-chemical properties (engineered size, concentration, agglomerated size in water, zeta potential, pH and age of the suspension, and oxidant production) were redundant in terms of their detectable linear interdependencies across different silver, copper, nickel, zinc and iron NMs.…”
Section: Project/publicationmentioning
confidence: 99%
“…Studies have shown that NPs can be imported into cells via endocytosis for smaller particles that are less than 120 nm (Conner and Schmid, ). Previous studies have suggested that biological activities, such as cellular uptake and health effects of NPs, are greatly affected by their size, shape ( Chithrani et al ., ; Chithrani and Chan, ) and surface charge (Berg et al ., ; Sayes et al ., ). Researchers explore novel synthesis methods to control these surface properties by using different capping agents (i.e.…”
Section: Introductionmentioning
confidence: 97%